A new species of Megophrys (Amphibia: Anura: Megophryidae) from Vietnam - Nguyen, Truong Quang; Pham, Cuong The; Nguyen, Tao Thien; Luong, Anh Mai; Ziegler, Thomas (Zootaxa, 2020)
A new species of Megophrys is described from Cao Bang Province, northeastern Vietnam based on morphological and molecular data. Morphologically, the new species is distinguishable from its congeners by a combination of the following characters: Size small (SVL 34.9–38.9 mm in males); tympanum visible; vomerine teeth absent; tongue not notched posteriorly; male with a single vocal sac; toes with rudimentary webbing; subarticular tubercles and lateral fringes absent on all digits; nuptial pads present on fingers I and II in males, with spicules; dorsal skin with scattered granules and tubercles; flank with tubercles; dorsum with a X-shaped dorsal ridge; dorsolateral folds prominent; a small horn-like tubercle present at the outer edge of the eyelid; dorsal surface yellowish brown with a dark brown triangle between the eyes, and a dark brown marking along the X-shaped ridge on the back. In the phylogenetic analyses, the new species is unambiguously nested within the subgenus Panophrys with interspecific uncorrected genetic p-distances (16S rRNA gene) varying from 4.26% (compared with M. rubrimera) to 10.80% (compared with M. acuta).